Indonesian EFL Undergraduate Students' Interest Towards Metacognitive Strategy in Reading Academic Comprehension - Patrick Adtya Pratama Sinom; Paulus Kuswandono (Yayasan Visi Intan Permata, 2022)
Academic reading comprehension is affected by many factors. This research was focused on understanding academic reading comprehension from the perspectives of interest and metacognitive strategy. This research aimed to find a correlation between students’ interests and metacognitive strategy (before and during reading academic comprehension). The research was conducted at Sanata Dharma University, Yogyakarta. There were 27 students who participated in this research. The survey design using a correlational study was applied to analyze the data from the survey-open and close-ended questionnaires. Pearson coefficient correlation was used in exposing the correctional status. The result of the current study showed that there is a positive moderate correlation between students’ interest and metacognitive strategy in reading academic comprehension. Supported by an open-ended data interpretation, this research found that both interest and metacognitive strategy are correlated especially in terms of self-motivation and self-regulation, mood, and strategy employment in reading academic comprehension. This research would have a great theoretical and practical contribution to the English language department, especially for teachers and students in terms of reading academic comprehension.